2008
DOI: 10.1098/rspb.2008.0705
|View full text |Cite
|
Sign up to set email alerts
|

Environmental variation at the onset of independent foraging affects full-grown body mass in the red fox

Abstract: The period following the withdrawal of parental care has been highlighted as a key developmental period for juveniles. One reason for this is that juveniles cannot forage as competently as adults, potentially placing them at greater risk from environmentally-induced changes in food availability. However, no study has examined this topic. Using a long-term dataset on red foxes (Vulpes vulpes), we examined (i) dietary changes that occurred in the one-month period following the attainment of nutritional independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…The body mass of British male foxes has been reported to exhibit a stronger relationship with July rainfall ('worm nights') than the female body mass . The fact that the female body mass does not increase as much as the male body mass during years of ample food indicates that the two sexes are subject to different selection forces as suggested by Soulsbury et al (2008). This was supported by a study on foxes in Bristol (UK), where heavier males were found to hold larger territories, exert a greater boundary pressure on smaller neighbours, and to invest more effort when searching for extra mates by traversing a wider area .…”
Section: Rump Fat Thicknesssupporting
confidence: 61%
See 1 more Smart Citation
“…The body mass of British male foxes has been reported to exhibit a stronger relationship with July rainfall ('worm nights') than the female body mass . The fact that the female body mass does not increase as much as the male body mass during years of ample food indicates that the two sexes are subject to different selection forces as suggested by Soulsbury et al (2008). This was supported by a study on foxes in Bristol (UK), where heavier males were found to hold larger territories, exert a greater boundary pressure on smaller neighbours, and to invest more effort when searching for extra mates by traversing a wider area .…”
Section: Rump Fat Thicknesssupporting
confidence: 61%
“…It seems that several factors such as climate, latitude, population density, food availability and genetic components can affect the weight and body length of foxes (Cavallini 1995;Gortazar, Travaini, and Delibes 2000;Englund 2006;Lindström 1983;Lloyd 1980;Kolb and Hewson 1974;Meiri, Dayan, and Simberloff 2004;Soulsbury et al 2008). Currently, very little is known about the underlying mechanisms of fox size on a local scale.…”
Section: The Three Collections Of Foxesmentioning
confidence: 99%
“…It is well known that many factors affect growth over the course of an individual's lifespan, primarily those related to food intake (such as whether being fed by carers, and food availability, Russell et al 2002;Soulsbury et al 2008) and trade-offs over resource allocation (such as whether an individual is investing in growth or reproduction, Stamps 1993;Arendt 1997). Simple growth curves do not take account of these factors and calculate only one growth rate parameter over the lifespan (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Through this method regular attenders are easily identifiable, though those visiting infrequently could be mis-identified as new. We restricted our data to full grown individuals (>6 months: Soulsbury et al 2008). …”
Section: Data Collectionmentioning
confidence: 99%
“…So reliance on feeding site could vary seasonally depending on natural food availability (Tsukada & Nonaka 1996) or on intrinsic factors. For example, attendance may be highest during spring/summer when parents or other group members are food provisioning cubs (Soulsbury et al 2008). In contrast, infrequent attenders at feeding sites would be expected most often during autumn and winter, coincident with dispersal and reproductive movements (Baker et al 2001;Soulsbury et al 2011).…”
Section: Introductionmentioning
confidence: 99%